(untitled) (Experimental biology, 2016)
This article addresses the issue of biodiversity conservation of rare endemic species of Ile-Balkhash region Lonicera iliensis Pojark. by creating seed collections. Seeds were collected from three natural populations of Lonicera iliensis in the Almaty region. It was shown that the viability of the honeysuckle seeds significantly depends on the storage temperature. Lonicera iliensis seed storage for 3 years in uncontrolled conditions (at room temperature) resulted in loss of viability, whereas at + 4°C laboratory germination remained at 49.0-78.3% of initial germination. It was found that the seed stratification after storage at low and ultra-low temperatures (-18°C ...-20°C and -196°C) have a positive effect on their germination. Laboratory germination of honeysuckle Ili seeds stored for three years at 18°C ...-20°C and then held 1-week stratification was 63.3-86.1% of the initial. Laboratory germination of seeds after deep-freezing combined with 1 week of stratification remained at 87.4-100% of control seeds germination. The collections of Lonicera iliensis seeds from three natural populations were established at various storage conditions (+4°C, -18°C ...-20°C and -196°C ), which can be used to restore this species in nature, as well as for the exchange of genetic material.